FERTILIZANTES PARA CULTIVO ORGÂNICO DE ALFACE (Lactuca sativa L) - RODRIGUES, Pedro Henrique Dias Rodrigues,; HAYD, Norton Hayd Rego,; ESPINDOLA, Gabriella Alemida dos Santos Espindola,; DIONÍZIO, Jéssica Dionizio Vieira,; STRANG, Rafael de Sá Strang,; BARROS, Luís Gustavo Silva Barros Filho, (ANAIS DO ENIC, 2024)
-